Analisis Pengaruh Sarana Prasarana Dan Motivasi Kerja Pegawai Terhadap Semangat Kerja Pegawai Pada Dinas Pengendalian Penduduk Dan Keluarga Berencana Kota Sibolga - Ananda Pertiwi Pohan; Mansur Tanjung; Dicky Syahputra Lubis (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of work facilities and work motivation on employee morale at the Department of Population Control and Family Planning of Sibolga City. The research employed a quantitative approach with an associative research design. The population consisted of 42 employees, all of whom were selected as the sample using a saturated sampling technique. Data were collected through questionnaires, interviews, and observations, and analyzed using multiple linear regression with SPSS. The results indicate that work facilities and work motivation have a positive and significant effect on employee morale, both partially and simultaneously. The coefficient of determination value of 0.471 shows that 47.1% of the variation in employee morale can be explained by these two variables, with work facilities being the more dominant factor. Therefore, improving work facilities and employee motivation is essential to enhance employee morale.